Imerslund-Gräsbeck Syndrome: A case report - Şen, Çiğdem; Aygün, A. Denizmen; Gürgöze, Metin K.; Kılıç, Mehmet (Fırat University, 2001)
The Imerslund-Gräsbeck syndrome is a rare inherited disorder characterized by a megaloblastic anemia due to a selective vitamine B12 malabsorption in association with a mild proteinuria. A twenty-two month-old-boy who had diarrhea since the last year, is admitted to our hospital with vomiting and fever. Proteinuria, megaloblastic anemia, steatorrhea and malnutrition were detected. The diagnosis of Imerslund-Gräsbeck disease was performed on the basis of association of typical megaloblastic cells in the bone marrow and favourable outcome with parenteral vitamine B12 administration. In addition, our patient had no folat deficiency, no anti-intrinsic factor antibodies and no intrinsic factor deficiency.

Imerslund Gräsbeck sendromu selektif vitamin B12 malabsorbsiyonu sonucu megaloblastik anemi gelişen, orta derecede proteinürinin eşlik ettiği kalıtsal geçişli nadir bir hastalıktır. Bir yıldan beri devam eden ishali olan yirmi iki aylık erkek çocuğu, kusma, ateş yakınması ile kliniğimize getirildi. Yapılan tetkiklerinde megaloblastik anemi, proteinüri, steatore, ve malnütrisyon saptandı. Kemik iliğinde megaloblastik değişiklerin varlığı ve parenteral B12 vitamini tedavisi ile iyileşmenin hızlı olmasının birlikteliği ile Imerslund-Gräsbeck sendromu tanısı konuldu. Ayrıca hastamızda folat eksikliği, intrensek faktör eksikliği ve intrensek faktör antikorlarına rastlanmadı
IMERSLUND GRÄSBECK SENDROMU: OLGU SUNUMU